20th century photographers : interviews on the craft, purpose, and the passion of photography - Schaub, Grace; Schaub, George (Routledge, 2015)
This book is a compilation of interviews and essays that cover a broad range of photographers and photographic disciplines. Each photographer profiled made a living by concentrating on a specific aspect of the craft, but in doing so transcended their livelihood to become recognized for more than the type of images they created. Each had a distinct ""style,"" creative approach, dedication to the craft, point of view about themselves and the world. These interviews were conducted during a seminal period in the shift from film to digital and from print reproduction to global distribution on the I
Keywords: Photographers : History : 20th century : Interviews; Photography : History : 20th century